Parental knowledge and awareness of food allergies among their children at Hospital Pakar Universiti Sains Malaysia (HPUSM) - Zainuddin, Siti Zulaikha (Universiti Sains Malaysia, 2025)
Food allergies are an increasingly common public health concern that significantly affects the quality of life of children. This study aimed to assess the level of parental knowledge and awareness of food allergies among their children at Hospital Pakar Universiti Sains Malaysia (HPUSM). A cross-sectional study was conducted among 218 parents who were selected through convenience sampling and completed a structured questionnaire based on previous validated research. Findings revealed that 39.0% of parents had a moderate level of knowledge, 26.1% had good knowledge, while 34.9% demonstrated poor knowledge. In terms of awareness, 53.7% had moderate awareness, 32.6% had good awareness, and 13.8% had poor awareness. A significant moderate positive correlation was found between knowledge and awareness scores (r = 0.519, p < 0.001). The results highlight the need for effective educational interventions aimed at improving parental understanding of food allergy symptoms, causes, prevention, and management. Education plays a vital role in equipping parents with accurate information and appropriate management strategies. This study recommends implementing evidence-based educational programmes to support better food allergy management among children